Réponses

2014-01-08T19:37:18+01:00
Bonsoir,


1) 9x - 1 = 0
9x = 1
x = 1/9

2) 2x - 2 = 3x
2x - 3x = 2
-x = 2
x = -2

3) -3x + 3 = -6x + 3
-3x + 6x = 3 - 3
3x = 0
x = 0/3
x = 0

4) x + 4 - 3x = 8
x - 3x = 8 - 4
-2x = 4
x = 4/(-2)
x = -2

5) 4x² + 4x - 4 = 2 - 3x + 4x²
4x² + 4x + 3x - 4x² = 2 + 4
7x = 6
x = 6/7

6) 9x² + 24x + 16 = 0
(3x + 4)² = 0
3x + 4 = 0
3x = -4
x = -4/3
2014-01-08T20:06:36+01:00
Résolution d'équations :
9 x - 1 = 0
9 x = 1
x = 1/9

2 x - 2 = 3 x
2 x - 3 x = 2
-x = 2
x = -2

-3x + 3 = -6x + 3
-3x + 6x = 3 - 3
3x = 0
x = 0/3 = 0

x + 4 - 3x = 8
x - 3x = 8 - 4
-2x = 4
x = 4/-2
x = -2

4x² + 4x - 4 = 2 - 3x + 4x²
4x² + 4x + 3x - 4x² = 2 + 4
7x = 6
x = 6/7

9x² + 24x + 16 = 0                 identité remarquable 9x² +24x +16 = (3x+4)²
(3x + 4)² = 0
3x + 4 = 0
3x = -4
x = -4/3